The Effect of Peer Drilling on 10th Grade Student’s Vocabulary Mastery - Ishak Ishak Ishak; Euis Yanah Mulyanah; Andi Wijaya - (Journal of English Language Studies, 2019)
This research is expected to know whether there is significant different score of vocabulary test before and after treatment has been given. This research is a quasi-experimental design where the population is Tenth Grade of SMA Muhammadiyah 2 Cipondoh Tangerang. The researcher took sample from X.4 class as control class and X.5 class as experiment class. The sample is 40 students for each class. In collecting the data, the researcher used interview, pretest and posttest of vocabulary and applied peer drilling as a technique in teaching learning process. Furthermore the researcher calculated the data by using t test. In addition the hypothesis test result at the degree of significance 0.05 indicates that in control group H₀ is rejected and H₁ is accepted because t count > t table (4.70 > 1.684) where there is a little significant difference of student’s vocabulary test whereas in experiment class, H₀ is rejected and H₁ is accepted with t count > t table (18.08 > 1.684). It means that there is more significant difference of student’s vocabulary test. In other words, Peer Drilling can improve student’s vocabulary mastery in the classroom.